Improving Healthcare Delivery System using Business Intelligence - Rathore, Prathviraj Singh; Sharma, B. K. (Journal of ISMAC, 2022)
Healthcare organizations focus more on data and information for the wellbeing of the patients. They also look forward to improving the business process, business trends, and operational performance using Business Intelligence tools. Business Intelligence tools are used in collecting data, storing data, examining data, and formatting records in an easy way. Business Intelligence can give new business insights and analysis-based predictions. These new business insights help managers and supervisors in decision-making. Now many healthcare organizations are using Business Intelligence to improve the quality of healthcare services and the healthcare delivery system over the competitiveness in the global healthcare scenario. This paper proposes a reasonable structure of healthcare organizations and the result analysis of OPD and IPD patients in the eight healthcare organizations.